Transsynaptic Long-Term Potentiation in the Hippocampus of Behaving Mice - Romero-Barragán, Maria Teresa; Gruart, Agnes; Delgado-García, José M. (Frontiers in Synaptic Neuroscience, 2022)
Long-term potentiation (LTP) is an experimental procedure that shares certain mechanisms with neuronal learning and memory processes and represents a well-known example of synaptic plasticity. LTP consists of an increase of the synaptic response to a control stimulus following the presentation of a high-frequency stimulation (HFS) train to an afferent pathway. This technique is studied mostly in the hippocampus due to the latter’s high susceptibility and its laminar nature which facilitates the location of defined synapses. Although most preceding studies have been performed in vitro, we have developed an experimental approach to carry out these experiments in alert behaving animals. The main goal of this study was to confirm the existence of synaptic changes in strength in synapses that are post-synaptic to the one presented with the HFS. We recorded field excitatory post-synaptic potentials (fEPSPs) evoked in five hippocampal synapses, from both hemispheres, of adult male mice. HFS was presented to the perforant pathway (PP). We characterized input/output curves, paired-pulse stimulation, and LTP of these synapses. We also performed depth-profile recordings to determine differences in fEPSP latencies. Collected data indicate that the five selected synapses have similar basic electrophysiological properties, a fact that enables an easier comparison of LTP characteristics. Importantly, we observed the presence of significant LTP in the contralateral CA1 (cCA1) area following the control stimulation of non HFS-activated pathways. These results indicate that LTP appears as a physiological process present in synapses located far away from the HFS-stimulated afferent pathway.